Emergence of infectious diseases risk and issues for societies - Figuié, Muriel; Morand, Serge 1959- (Éditions Quae, 2018)
From SARS to avian influenza, Ebola virus and MERS-CoV, infectious diseases have received increasing attention in recent decades from scientists, risk managers, the media and the general public. What explains the constant emergence of infectious diseases? What are the related challenges? In five chapters, experts from different scientific fields analyse the ecological, social, institutional and political dynamics associated with emerging infectious diseases. This book discusses how the concepts, scientific results and action plans of international or governmental organizations are constructed and coordinated. In clear straightforward language, this book explores the continuities and discontinuities that occur with emerging infectious diseases, both in terms of collective action and in our relationship to the biological world
Literaturverzeichnis: Seite 113-126
Keywords: Infektionskrankheit